Pelatihan Digital Marketing untuk Meningkatkan Daya Saing Produk Lokal - Febriani, Rizki Anisa (Jurnal Karya Nyata Pengabdian, 2024)
The advancement of digital technology has brought significant changes in the business world, including for micro, small and medium enterprises (MSMEs). However, there are still many MSMEs that have not utilised digital marketing optimally to improve the competitiveness of their products. This article discusses the implementation of a digital marketing training programme that aims to improve the marketing skills of MSME players in promoting local products. The training involved various techniques, such as the utilisation of social media, e-commerce platforms, and relevant content strategies. The results of this programme show an increase in MSME players' understanding and ability to utilise digital media, which in turn helps expand their market and increase sales.